Mainliner's survival guide to the post-denominational world - Penwell, Derek (St. Louis : Chalice Press, 2014)
The Mainliner's Survival Guide to the Post-Denominational World considers how the declining church should live into the hope of its legacy by living out the Gospel's radical nature with reckless abandon. In a world where the fastest growing religious self-designation among emerging generations is none, the hope of the church may lie in worrying less about the survival of the church and aiming more toward living like Jesus.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United States -- Church history; Christianity -- 21st century; RELIGION / Christian Church / Leadership; RELIGION / Christianity / History; Electronic books